Role of Professional Learning Communities in Promoting Teachers' Life Skills in Palestine - Al-Deek, Samia Omar; Hazboun, Grace Nasri; Abed, Ghadeer Thabet; Naser, Inas (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the role of professional learning communities in promoting the life skills of teachers in the Palestinian Governorates. The study population consisted of (8831) subjects in all public schools at Naplus, South Hebron, and Ramallah Governorates for the academic year 2021-2022. The researchers used a descriptive Methodology. Data from the study was collected using a questionnaire containing (45) items distributed to four domains. A cluster sample of (372) male and female teachers from the governorates in Palestine was chosen. Findings of the study disclosed that professional learning communities, to a large degree, play a role in promoting teachers' life skills in the Palestinian governmental schools (82.1%). The results also showed that there were no significant statistical differences at the level (α≤0.05) in the sample's responses towards the role of the professional learning communities in promoting life skills of the teachers working at the Palestinian governmental schools due to the variable of the gender, specialization, academic qualification, and directorate. Considering these findings, the study recommends activating the role of professional learning communities in promoting life skills with a special focus on teachers' social skills through training and practice.
Keywords: Professional Learning Communities; Life Skills; Palestine State